Factors affecting procurement planning in different government sectors of Bangladesh: a case study of civil aviation authority of Bangladesh - Afroz, Zakia (BARC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.